Human development and capability building in the Niger Delta: Issues and challenges - Okinono, Otega (MCSER Publishing, Rome-Italy, 2015)
Continuous destruction of the Niger Delta region of Nigeria environment by oil-related exploration, unemployment, human development and education has persistently caused unrest and violence.Despite the laudable strategies adopted by the government in ensuring lasting solution in the region, scholars have however criticized some of the strategies as not working and impacting in the lives of the target population.This paper therefore explores human development and capability issues in achieving sustainable community development in the region.In-depth interview was used to investigate the issues in six communities in three selected states and NDDC. The result of this study revealed that issues like insufficient funding, projects abandonment, community attitude and leadership style are the major impediments to sustainable human development in the Niger Delta.It is therefore recommended that both governmental and non-governmental developmental agencies should take into cognizance issues like proper funding, monitoring and evaluation of projects and community involvement in designing and implementation of development plans.Likewise, community should see themselves as developmental partners with development agencies by way of developing positive attitude and maintenance to developmental projects.